Synthesis and Characterization of TiO2-ZnO Nanocomposite Photocatalyst for the Removal of Basic Violet 14 as an Industrial Dye - Samad, Md. Abdullah Bin; Quayum, Emran; Hossain, Md. Amjad; Islam, Tajmeri S. A.; Khan, Mohammad Mahmudur Rahman (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2023)
Binary nanocomposites are one of the promising photocatalysts for the photodegradation of toxic industrial organic dyes which are used as dying agents in different industries including garments and textiles, leather, paint and varnish industries. For this study, TiO2-ZnO nanocomposites were fabricated by the hydrothermal process; where ZnSO4.7H2O is used as a precursor and TiO2 is used as a supporting material. The prepared TiO2-ZnO nanocomposites were calcined at three distinct temperatures 300 °C, 400 °C, and 500 °C. These composite materials were characterized by Scanning Electron Microscope (SEM), X-Ray Diffraction (XRD), Energy Dispersive X-Ray (EDX), and Fourier Transform Infrared (FTIR) analyzes. Basic Violet 14 (BV14), an industrial dye, was modelled to examine the photocatalytic role of TiO2-ZnO under different experimental setups such as calcined temperatures, catalyst loading, concentrations of the BV14 dye, pH, and light sources. TiO2-ZnO prepared at 500 °C acted as the best photocatalyst among three nanocomposites and the prepared TiO2-ZnO worked better than solitary TiO2 and ZnO to decolorize the BV14 dye. In the presence of sunlight, UV light, and visible light the percentages of degradation of BV14 were found to be 81.78 %, 69.58 %, and 31.24 %, respectively. The maximum photodegradation corresponded to 0.175 g/100 mL of suspension of nanocomposite with an initial 3.0×10−5 M of BV14 having solution pH 6.88. The surface reaction constant and Langmuir-Hinshelwood adsorption constant were obtained to be 5.5×10−8 mol.L−1.min−1 and 1.7×108 L.mol−1, respectively. Copyright © 2023 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).